Type 2 Diabetes Mellitus in Ayurveda w.s.r to Medovaha Srotas - Saranya K; Ratheesh P; Surej Subash; Vinitha C; Nimisha Michael (AYUSHDHARA, 2024)
Non-communicable diseases (NCDs) kill 41 million people each year, which is equivalent to 74% of the entire deaths globally. According to the statistics from the International Diabetes Federation, in the year 2021 there are 537 million adults (20-79 years) living with diabetes i.e., 1 in every 10 persons is said to be diabetic It is high time for the approach to Diabetes mellitus is remodelled. Prameha is the most commonly correlated disease with diabetes mellitus. Prameha is a Medovaha srotodushti vikara and Prameha purvarupa is seen in Medovaha srotodushti avastha. Avyayama, Divaswapna, Kaphavardhaka ahara vihara etc are the causative factors for Prameha. Ayurveda always follow a holistic approach in treatment aspect. Being lifestyle disorder diabetes also need that type of approach. Our Acarya have explained Prameha chikitsa emphasising the importance of modifying the food and lifestyle of the patient. From that it is clear that diabetes cannot be managed simply with medication. Lifestyle is also important in managing this disease. Our target group is not only diabetic patients but also people who are in their pre-diabetic stage. Ayurvedic management of diabetes mellitus with respect to Prameha is still an unexplored area. Early detection, analysis and wholistic approach in this condition may make milestones in reversing this condition in many populations or managing well in the others. Deeper understanding of Prameha is needed.